الطلاق في ضوء الشريعة الإسلامية " المقصد والحكمة الشرعية" (Comprehensive Journal of Science, 2026)
This study aims to examine the legal and religious foundations of divorce in Islamic law, focusing on its objectives, conditions, and types, as well as the social and economic consequences that follow. The research adopts a descriptive-analytical approach, relying on textual analysis of primary sources from the Qur’an, Sunnah, and classical jurisprudential texts, alongside contemporary scholarly interpretations. The findings reveal several key aspects: the conditions required for a valid divorce, including the competence and intent of the husband and the status of the wife; the differentiation between sanctioned (sunnī) and innovative (bid‘ī) forms of divorce; and the social and economic impacts on women and families. The study also highlights the misuse of divorce in contemporary society, such as hasty triple divorces or divorces issued without observing the proper legal and ethical guidelines, and stresses the importance of adhering to the objectives of Shariah to preserve family stability and protect the rights of all parties involved.
Keywords: Divorce, Islamic Law, Shariah Objectives, Social Impact, Women’s Rights, Family Stability